Halal Product Process Assistance Training to Improve Halal Certification of Micro Small Enterprises - Nur Aini; Annisaningrum Yuliastuti; Endang Hadiyanti; Ratna Yulika Go; Rizka Tesara Go (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
Training and mentoring on the halal product process aims to provide understanding and skills to PPH companions, who will then pass on to business actors in applying halal principles in all stages of production, from raw materials to finished products. With appropriate training and mentoring, business actors can understand the importance of halal products and manage production well to meet halal certification requirements. In the long run, halal products will have added value because they are considered safer and more trustworthy by consumers who prioritize product quality and religious aspects. The Halal Resource Development Study and Development Center (PK-PSDH) ITB Ahmad Dahlan Jakarta carried out training and mentoring activities on May 9-12, 2022, attended by 159 participants. Based on the results of the activity, as many as 279 products have obtained their halal certification, 90 data are still in submission, 31 data are submitted, 67 data are finished with LP3H, 31 data are returned, 19 data are returned to the Fatwa Commission, 59 data are canceled, and 3 data are sent to the fatwa commission. Halal training and mentoring will continue to be carried out in the future to assist business actors in improving product quality and consumer confidence, as well as increasing business competitiveness in the global market.